2020
DOI: 10.3390/foods9050608
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput 16S rRNA Gene Sequencing of Butter Microbiota Reveals a Variety of Opportunistic Pathogens

Abstract: Microbial contamination of dairy products with a high fat content (e.g., butter) has been studied insufficiently. No studies using modern molecular methods to investigate microbial communities in butter have been conducted so far. In this work, we used high-throughput sequencing and Sanger sequencing of individual bacterial colonies to analyze microbial content of commercially available butter brands. A total of 21 samples of commercially available butter brands were analyzed. We identified a total of 94 ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Given the protective effects of metabolizable sugars on Lactobacilli in acidic environment, L. taiwanensis CLG01 may survive better in the fermented food [ 35 ]. L. taiwanensis was detected as one of the most abundant Lactobacillus species in the butter [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the protective effects of metabolizable sugars on Lactobacilli in acidic environment, L. taiwanensis CLG01 may survive better in the fermented food [ 35 ]. L. taiwanensis was detected as one of the most abundant Lactobacillus species in the butter [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to stability, it is widely used in molecular identi cation, taxonomic studies, and phylogenetic and evolutionary studies [17]. Das et al [18], Egege et al [19], Hardy et al [20] and Syromyatnikov et al [21] in their studies had also shown the effectiveness and precision in using 16S rRNA gene sequence-based assay for the identi cation of bacterial isolates obtained from different samples. In our study, we used PCR sequencing of 16SrRNA gene to effectively con rm Staphylococcus saprophyticus strains previously identi ed using biochemical and phenotypic characterisation.…”
Section: Discussionmentioning
confidence: 99%
“…Due to stability, it is widely used in molecular identi cation, taxonomic studies, and phylogenetic and evolutionary studies [24]. Das et al [25], Egege et al [26], Hardy et al [27] and Syromyatnikov et al [28] in their studies had also shown the effectiveness and precision in using 16S rRNA gene sequence-based assay for the identi cation of bacterial isolates obtained from different samples. In our study, we used PCR sequencing of 16SrRNA gene to effectively con rm Staphylococcus saprophyticus strains previously identi ed using biochemical and phenotypic characterisation.…”
Section: Phylogenetic Analysis Of the S Saprophyticus Strainsmentioning
confidence: 99%